2017
DOI: 10.1002/jso.24828
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative fluid and hemodynamic management within an enhanced recovery pathway

Abstract: Goal-directed fluid therapy (GDFT) seeks to improve outcomes through individualized optimization of oxygen delivery using IV fluid and vasoactive infusions. Trials of GDFT show clinical benefits over traditional liberal fluid administration, but fail to demonstrate benefits when compared to a restrictive strategy within an optimized enhanced recovery protocol. The ideal monitors, hemodynamic goals, and fluid administration strategy are not well established but may be less important than rational application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 87 publications
0
15
0
Order By: Relevance
“…Prevailing evidence from our research group and others, has led to the notion of the "protocolised" perioperative "fluid-restrictive" approach [28][29][30] in order to reduce postoperative morbidity, including AKI. In this regard, our findings are consistent with the existing evidence reinforcing a strong association between fluid volume [31][32][33][34][35][36][37] and chloriderich fluid type [38][39][40][41] , and risk of AKI.…”
Section: Relationship With Previous Studiesmentioning
confidence: 99%
“…Prevailing evidence from our research group and others, has led to the notion of the "protocolised" perioperative "fluid-restrictive" approach [28][29][30] in order to reduce postoperative morbidity, including AKI. In this regard, our findings are consistent with the existing evidence reinforcing a strong association between fluid volume [31][32][33][34][35][36][37] and chloriderich fluid type [38][39][40][41] , and risk of AKI.…”
Section: Relationship With Previous Studiesmentioning
confidence: 99%
“…The combined physiologic effects of prone positioning and the risk of substantial blood loss pose patients undergoing multilevel spine surgery at high risk for intraoperative hemodynamic instability. GDFT is described as an approach to guide perioperative fluid administration in order to avoid fluid overload, organ hypoperfusion, hypoxia, and hypovolemia ( 35 , 36 ). This volume replacement strategy has been associated with more positive post-operative outcomes such as enhanced post-operative recovery and reduced length of hospital stay, occurrence of acute renal injury and infections ( 37 44 ).…”
Section: Physiologic Changes During Prone Positioningmentioning
confidence: 99%
“…A recent clinical trial found significantly less neurologic and renal injury when patients were maintained at their target BP rather than at a standard BP . Precision medicine is also seen in the implementation of enhanced recovery pathways, including continuous hemodynamic and oxygen delivery monitoring to mitigate organ ischemia through goal‐directed fluid therapy and/or the addition of inotropes or vasopressors while minimizing fluid overload …”
Section: Perspectives On Precision Medicine By Prnmentioning
confidence: 99%